Perlindungan dan Pertanggungjawaban Hukum atas Transfer Data Pribadi oleh Pemerintah Indonesia ke Amerika Serikat - Tania Fatmawati; Arman Tjoneng (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Technological developments and globalization have fueled increased exchange of personal data between countries, including cooperation between Indonesia and the United States in business sectors related to the transfer of data belonging to Indonesian citizens. However, differences in the legal systems between the two countries raise issues regarding protection and legal liability in the event of misuse of personal data abroad. The United States currently lacks a comprehensive federal personal data protection law, while Indonesia has Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), which affirms that personal data is a human right. This regulatory discrepancy raises questions about the extent to which Indonesian law can provide effective protection for its citizens' personal data outside its jurisdiction. This study uses a normative-juridical method with a regulatory and conceptual approach. The analysis was conducted on applicable regulations, international legal principles, and related academic sources. The study findings indicate that although the PDP Law provides a solid legal basis, its implementation remains suboptimal due to the lack of derivative regulations and an independent supervisory body. Therefore, the government's legal accountability mechanism for personal data breaches abroad is not yet functioning effectively. This study concludes that the Indonesian government must immediately establish an independent supervisory body for personal data protection, issue implementing regulations for the Personal Data Protection Law concerning the mechanism for data transfers between countries, and strengthen international collaboration to ensure the protection of Indonesian citizens' personal data in the destination countries.